Anodic reduction of electrodeposited polymethacrylates containing pendent sulfones. (16th September 2021) - Oto, Kota; Takasu, Akinori
Abstract: Anionic polymerization of a non-conjugated polar alkene, allyl methacrylate (AMA) was initiated by tert -BuLi ( t -BuLi) in toluene at −20 °C for 2 h in the presence of a bulky aluminum Lewis acid, methylaluminum bis(2, 6-di- tert -butyl-4-methylphenoxide) (MAD). Quantitative monomer consumption was confirmed and >99% of the expected poly(AMA) was obtained after reprecipitation using chloroform and methanol as good and poor solvents, respectively [ M n of 12.2 × 10 3 -21.6 × 10 3 with a molecular dispersity index ( M w / M n  = 1.70 -1.83 )]. A thiol-ene click reaction of the pendent ally groups with 1-butanethiol and subsequent Oxone-oxidation gave the poly(AMA) with pendent ternary units of sulfone, sulfoxide, and sulfide [ M n of 11.3 × 10 3 -26.0 × 10 3 with a molecular dispersity index ( M w / M n  = 1.43 -1.79 )]. Electrophoretic deposition (EPD) was performed as detailed in our previous report dealing with electrophoretic sulfone-containing non-ionic polymers, using a dispersion consisting of tetrahydrofuran (THF) and methanol (1/50, v/v). As we expected, the obtained poly(AMA) derivatives were deposited on an iron plate. However, 1 H NMR results surprisingly supported the simultaneous reduction of the pendent sulfone to sulfide after the deposition, which indicated that anodic reduction of sulfone-containing electrophoretic polymer had been demonstrated without the need for expensive commercially available reagents. Graphical abstract: Image 1 Highlights: Poly(allyl methacrylate)s with pendent sulfones prepared via anionic polymerization. The polymethacrylates showed electrophoretic deposition, accompanied with reduction. The unexpected anodic reduction was confirmed by X-ray photoelectron spectroscopy.